2018
DOI: 10.30880/ijie.2018.10.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Respiratory Symptoms, Spirometric Lung Patterns and Metal Fume Concentrations among Welders in Indoor Air-Conditioned Building at Malaysia

Abstract: Welding is one of the fundamental processes for metal joining in automotive industries and there is an increasing concern over occupational lung disease among welder due to exposure towards welding fumes. A lung disease questionnaire (ATS-DLD-78) was used to record the presence of respiratory symptoms among welders and in assessing lung function assessment, FEV1, FVC and FEV1/FVC are considered for identifying the lung condition; normal, obstructive or restrictive. The data were tabulated and subjected to logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…A pvalue was deemed statistically significant if it was less than 0.05. The frequency and descriptive statistics of socio-demographics collected in this pilot study, the correlation between respiratory-related symptoms and lung function among respondents, as well as the findings of multivariate regression, were established in other articles 41) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pvalue was deemed statistically significant if it was less than 0.05. The frequency and descriptive statistics of socio-demographics collected in this pilot study, the correlation between respiratory-related symptoms and lung function among respondents, as well as the findings of multivariate regression, were established in other articles 41) .…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the research team that participates in this project should be well-versed not only in the relevance of cultural questions before collecting data but also in considering the technical and semantic equivalence perspectives. A pilot test of the translated version questionnaire was conducted among automotive welders to provide extra rigour and validity to the Malay version questionnaire, and the study found that this translated questionnaire was useful as a tool in diagnosing respiratory problems among adult workers 41) .…”
Section: Translation Processmentioning
confidence: 99%